Recent Developments in Ring-Opening Copolymerization of Epoxides With CO2 and Cyclic Anhydrides for Biomedical Applications - Liang, Xue; Tan, Fei; Zhu, Yunqing (Frontiers in Chemistry, 2021)
The biomedical applications of polyesters and polycarbonates are of interest due to their potential biocompatibility and biodegradability. Confined by the narrow scope of monomers and the lack of controlled polymerization routes, the biomedical-related applications of polyesters and polycarbonates remain challenging. To address this challenge, ring-opening copolymerization (ROCOP) has been exploited to prepare new alternating polyesters and polycarbonates, which would be hard to synthesize using other controlled polymerization methods. This review highlights recent advances in catalyst development, including the emerging dinuclear organometallic complexes and metal-free Lewis pair systems. The post-polymerization modification methods involved in tailoring the biomedical functions of resultant polyesters and polycarbonates are summarized. Pioneering attempts for the biomedical applications of ROCOP polyesters and polycarbonates are presented, and the future opportunities and challenges are also highlighted.